Principios constitucionales de eficiencia, continuidad y calidad en la gestión de los gobiernos autónomos descentralizados. - Santillán Lucas, Alfredo Jacinto (2015)
This legal thesis entitled "Constitutional principles of good living, efficiency, continuity and quality in managing decentralized autonomous governments" had the purpose to analyze various problem areas generated about the services provided by these public authorities to the population in their respective jurisdictions, the same as justified conduct research, both for its impact in the context of the requirements of society, the need to improve the quality of governance. For this purpose, objectives, general and specific formulated, which lead to more research, are identified in the conclusions. The formulation of the hypothesis routed by the literature and field research. Data collection and information needed for hypothesis testing was carried out by conducting surveys and interviews to sectors of the population considered. The results of the field research showed that the hypothesis was positive, for he went on to show that it is relevant to reform Art. 3 of the Organic Code of Territorial Organization, Autonomy and Decentralization, which are incorporated into the base of principles, the following constitutional principles: efficiency, continuity and quality. The conclusions of the investigation, it was ultimately determined that it is necessary to complement the basis of general principles of COOTAD with the constitutional principles of efficiency, continuity and quality principles will undoubtedly regulate and guide the operation of the Decentralized autonomous governments depending on the requirements, interests and needs of the general population.